PENGEMBANGAN PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DALAM MENINGKATKAN KARAKTER - Suparto, Achmad (Jurnal Phederal Penjas, 2015)
According Midtlying (1992: 8) through the principles of mechanics swimmers can understand a swimming motion that is so effective that will help improve performance. Colwin (1997: 20) argues that the process of training in the sport swimming, basic knowledge of hydrodynamics and biomechanics are important elements that must be mastered by the coach to help swimmers improve speed.Furthermore freestyle, a basic stroke. This means renangan freestyle is a technique that should be taught prior to the swimmer, before learning swimming techniques butterfly, backstroke and breaststroke. For applications in biomechanics, movement freestyle summarize all the basic principles of biomechanics.Some opinions may be summarized that the coaches of sports swimming understand and master the principles of biomechanics is the most important factor in the preparation of the training program. This is because the sport is a kind of sport that moves a highly technical and complex must be trained to athletes throughout the training process, it takes not only physical ability to swim fast, but also requires a technical ability renangan good and true as a supporter.Therefore biomechanical approach would be very wise to come up with a new method of movement so that the effectiveness of the results of the movement will continue to rise so that the world record will continue to rise, although it is not as easy as turning the hand.